ผลของการอ้างอิงตนเองและความเกี่ยวพันสินค้าที่มีต่อเจตคติต่อโฆษณา เจตคติต่อสินค้า และการตั้งใจซื้อสินค้าที่ได้รับการสนับสนุนจากเสียงส่วนมากและเสียงส่วนน้อย - สุธาภรณ์ ขอศานติวิชัย (จุฬาลงกรณ์มหาวิทยาลัย, 2015)
This current study aims to explore factors that can enhance minority influence in consumer behaviors context. Specifically, we examined the impact of product involvement and self-reference effect on participants attitudes and behaviours toward products endorsed by either a minority or a majority. Participants were 200 Chulalongkorn University undergraduate students. They viewed ads for either high (smartphone, laptop computer) or low (soft drink, facial tissue) involvement products endorsed by either a majority (>80%) or a minority (<20%) of either their ingroups (i.e., Chulalongkorn University students, thus high self-reference) or outgroups (i.e., working adults in general, thus low self-reference). Participants then reported their attitude toward the ads, attitude toward the products, and intention to buy the products. Data were analyzed using three-way MANOVA. Results showed that the high-involvement products endorsed by the ingroup minority were rated as positively as when they were endorsed by the ingroup majority. Moreover, high involvement products endorsed by the ingroup minority, compared with those endorsed by the outgroup minority, were rated significantly more positively on the three dependent variables. These findings suggest that, when product involvement is high, individuals are more willing to listen to opinion minorities who are perceived as part of their ingroup.